Evaluación de la reproducción masiva de nematodos entomopatógenos (Steinernema spp y Heterorhabditis spp) en larvas de gallina ciega (Phyllophaga spp) bajo condiciones controladas. - Arteaga Alarcón, Nohely Maite (2015)
The research was conducted in the laboratory and greenhouse State Technical University Quevedo located at Km 1 Vía Quevedo to Santo Domingo. The overall objective was to study the mass reproduction of entomopathogenic nematodes Steinernema and Heterorhabditis feltiae bacteriophora and assess its effectiveness as microbial control larval grubs "Phyllophaga spp" under controlled conditions. The specific objectives were to identify the effectiveness of each of these entomopathogenic nematodes as an alternative to combat grubs. To analyze the statistical test results "Chi Square" was used effected seven frequencies at intervals of 15 days to play and efficacy in laboratory and four frequencies for research in nursery. According to the results obtained in this study led to the use of entomopathogenic nematodes of the genus Heterorhabditis bacteriophora represents a good alternative for the control of larval grubs, Phyllophaga spp., In laboratory and greenhouse conditions. In the laboratory 96% efficiency was obtained with Heterorhabditisbacteriophora; as emissions level 80% efficiency was obtained. The nematodes of the genus Steinernema feltiae in all evaluated variables were lower than those obtained with nematodes of the genus Heterorhabditis bacteriophora. While research in the greenhouse determined less effective in controlling larvae of white grubs because nematodes must travel a greater distance to search for infest insects. We recommend reproducing gender nematodes Heterorhabditis bacteriophora by its greater reproducibility and efficiency in the natural control of insects and thereby contribute to preserving the environment.